Changes in Outdoor Workers' Sun-Related Attitudes, Beliefs, and Behaviors: A Pre–Post Workplace Intervention - Rye, S.; Janda, M.; Stoneham, Melissa; Crane, P.; Sendall, M.; Youl, P.; Tenkate, T.; Baldwin, L.; Perina, H.; Finch, L.; Kimlin, M. (Lippincott Williams and Wilkins, 2014)
Objective: To evaluate changes in outdoor workers' sun-related attitudes, beliefs, and behaviors in response to a health promotion intervention using a participatory action research process. Methods: Fourteen workplaces across four outdoor industry types worked collaboratively with the project team to develop tailored sun protection action plans. Workers were assessed before and after the 18-month intervention. Results: Outdoor workers reported increases in workplace support for sun protection (P < 0.01) and personal use of sun protection (P < 0.01). More workers reported seeking natural shade (+20%) and wearing more personal protective equipment, including broad-brimmed hats (+25%), long-sleeved collared shirts (+19%), and long trousers (+16%). The proportion of workers reporting sunburn over the past 12 months was lower at postintervention (-14%) (P = 0.03); however, the intensity of reported sunburn increased. Conclusions: This intervention was successful in increasing workers' sun protective attitudes, beliefs, and behaviors.